Prevalence of metabolic syndrome among middle-aged and elderly adults in China: current status and temporal trends. (19th May 2018) - Li, Wenzhen; Song, Fujian; Wang, Xiaojun; Wang, Longde; Wang, Dongming; Yin, Xiaoxv; Cao, Shiyi; Gong, Yanhong; Yue, Wei; Yan, Feng; Zhang, Hong; Sheng, Zhenjie; et al.
Abstract: Background: Metabolic syndrome (MetS) is a cluster of major risk factors for cardiovascular diseases. We aimed to estimate prevalence and distribution of MetS among middle-aged and elderly adults in China. Methods: The present analysis used data from a national study in 2014–2015. We defined MetS by different definitions, and compared results of the present study and previous nationally representative studies to illustrate possible temporal changes in MetS prevalence. Results: The estimated prevalence of MetS was 18.4% by the ATP III criteria, 34.0% by the revised ATP III criteria, and 26.9% by IDF criteria. The prevalence was higher in women, older adults, those with lower education level, and in economically developed regions. Contrasting with previous national studies, adults in urban areas had a lower rate of MetS than those in rural areas (odds ratio 0.94; 95% CI 0.92−0.97). Rural adults had worse deterioration or less improvement in abdominal obesity, overweight, hypertension, and high fasting plasma glucose, than urban adults, which was particularly striking for women. Conclusion: While measures to prevent and control cardiovascular diseases need to be strengthened in China, rapid increasing risk factors among rural residents and women should be prioritized in making public health policy decisions. KEY MESSAGES: Our study assessed prevalence and temporal changes of MetS among Chinese population with the most recently completed and the largest sample size. The current prevalence of MetS was higher in women, older adults, those with lower education level, and in economically developed regions and the CVD risk factors among rural residents and women should be prioritised in making public health policy decisions. A comparison of results of the present study and previous national studies showed that rural adults had worse deterioration or less improvement in abdominal obesity, overweight, hypertension, and high fasting plasma glucose, than urban adults, which was particularly striking for women.